Hypersensitivity- An Update - Mohit Das; Abhaya Chandra Das; Sourav Panda; Rashmita Nayak; Rinkee Mohanty; Gatha Mohanty (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dentinal hypersensitivity (DHS) can be defines as a short sharp pain that occurs as a response to variousstimuli on exposure of dentinal tubules to the external environment and which cannot be described as anyother disease. The most important part of the treatment is to identify the etiology behind the sensitivity andtreating the condition accordingly. Differential diagnosis may include pulpitis, carious teeth, chipped tooth,cracked tooth syndrome etc. The treatment modalities depend upon whether the sensitivity is due to gingivalrecession, tooth wear lesion or periodontitis or related causes. This review highlights various strategies tocounter this disease as well discusses various desensitizing agents recently in use like Novamin, Biomin,Calcium phosphate dentifrices, Nanoparticles and herbal desensitizing agents.